Effect of sulfidation on nitrobenzene removal from groundwater by microscale zero-valent iron: Insights into reactivity, reaction sites and removal pathways. (January 2023) - He, Kai; Sun, Rui; Yang, Dezhi; Wang, Shuchen; Shu, Junjie; Wan, Wubo; Pan, Ying; Qin, Fengyang; He, Feng; Liang, Liyuan
Abstract: While it has been recognized that sulfidation can effectively improve the reactivity of microscale zero valent iron (mZVI), there is limited understanding of nitrobenzene (ArNO2 ) removal by sulfidated mZVI. To understand the reduction capacity and pathway of ArNO2 by sulfidated mZVI, ball-milling sulfidated mZVI (S-mZVI bm ) with different S/Fe molar ratios (0–0.2) was used to conduct this experiment. The results showed that sulfidation could efficiently enhance ArNO2 removal under iron-limited and iron excess conditions, which was attributed to the presence of FeSx sites that could provide higher Fe(0) utilization efficiency and stronger passivation resisting for S-mZVI bm . The optimum ArNO2 reduction could be obtained by S-mZVI bm with S/Fe molar ratio at 0.1, which could completely transform ArNO2 to aniline (ArNH2 ) with a rate constant of 4.36 × 10 −2 min −1 during 120-min reaction. FeSx phase could act as electron transfer sites for ArNO2 reduction and it could still be reserved in S-mZVI bm after reduction reaction. The product distribution indicated that sulfidation did not change the types of reduction products, while the removal of ArNO2 by S-mZVI bm was a step-by-step reduction progress along with the adsorption of ArNH2 . In addition, a faster reduction of ArNO2 in groundwater/soil system further demonstrated the feasibility of S-mZVI bm in the real field remediation. Graphical abstract: Image 1 Highlights: Sulfidation significantly enhanced nitrobenzene removal by mZVI bm . Fe(0) utilization of S-mZVI bm for nitrobenzene reduction was higher than that of mZVI bm . FeSx phase acted as electron transfer sites for nitrobenzene reduction and still reserved after reaction. Nitrobenzene removal by S-mZVI bm included a multi-step reduction process and adsorption of aniline. S-mZVI bm exhibited a faster nitrobenzene removal in groundwater/soil system.